Pengaruh Penggunaan Video Pembelajaran Pendidikan Pancasila terhadap Hasil Belajar Siswa Kelas 4 Bab 4 Pola Hidup Gotong Royong SD Islam AlHikmah - Annur Rochmah Fitriyanti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the effect of using instructional videos on students’ learning outcomes in the subject of Pancasila Education, specifically Chapter 4: "The Gotong Royong Way of Life" at Al-Hikmah Islamic Elementary School. The background of this research is based on the low interest and understanding of students due to the dominance of lecture-based teaching methods. The research method used is an experimental method with a non-equivalent control group design. The research subjects were 4A students as the experimental group and 4B students as the control group. Data collection techniques involved tests in the form of pre-tests and post-tests. The results showed an increase in the average learning outcomes in the experimental class from 45.39 to 84.17, while the control class increased from 53.05 to 71.78. The t-test results showed a t-value of 10.383, which is greater than the t-table value of 2.019, indicating that the alternative hypothesis is accepted. The relative effectiveness level also falls into the high category, at 69.70%. It can be concluded that the use of instructional videos has a significant effect on improving students’ learning outcomes. This study is expected to serve as a reference for teachers and schools in selecting more engaging and effective learning media
Entry oleh Arif 2026 Maret 25
Keywords: Instructional Video; Pancasila Education; Learning Outcomes; Gotong Royong Way of Life.